Development of Study Program Performance Assessment Application Using SCRUM Method - Denny Jean Cross Sihombing (STMIK Budi Darma, 2023)
This research aims to develop an innovative and efficient application for study program performance assessment to monitor and improve higher education's academic and management quality. The development method used is Scrum within a flexible and adaptive Software Development Life Cycle (SDLC) framework. The application includes features such as lecturer performance survey by students, lecturer and course evaluation, student achievement archive, lecturer attendance monitoring, and research management. The data collected from this application provides comprehensive insights for data-driven decision-making in academic management. The results show that using the Scrum method provides significant benefits by increasing the efficiency of performance management, simplifying administrative processes, and increasing student participation in providing feedback. The application also increases transparency and accountability among lecturers, teaching staff, and students. The successful application of Scrum in developing this application influenced positive outcomes, including the efficiency and transparency of academic evaluation. User trials showed a positive response, with approximately 92% of users finding the application interface easy to navigate and informative. Lecturers also reported the app's help in monitoring student progress. These results confirm the app's potential to support informative decision-making and enhance the learning experience in an academic environment